2020
DOI: 10.1101/2020.05.03.074765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-Synuclein aggregation intermediates form fibril polymorphs with distinct prion-like properties

Abstract: α-Synuclein (α-Syn) amyloid fibrils in synucleinopathies (such as Parkinson's disease (PD), multiple system atrophy (MSA)) are structurally and functionally different, reminiscent of prion-like strains. However, how a single protein can form different fibril polymorphs in various synucleinopathies is not known. Here, we demonstrate the structure-function relationship of two distinct α-Syn fibril polymorphs, the pre-matured fibrils (PMF) and helixmatured fibrils (HMF) based on α-Syn aggregation intermediates. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…These contain highly exposed hydrophobic surfaces and are potentially more toxic than less ordered PMFs. These polymorphs display not only structural differences but also exhibit different biological activities [252]. A similar study involving the identification of the aggregation intermediates in the presence of phospholipid membrane revealed that prefibrillar species contain two loop regions with residues 57 to 61 and 71 to 80 [305].…”
Section: Phase Separation and Nucleation: Molecular Basis Of Fibril Polymorphismmentioning
confidence: 93%
See 3 more Smart Citations
“…These contain highly exposed hydrophobic surfaces and are potentially more toxic than less ordered PMFs. These polymorphs display not only structural differences but also exhibit different biological activities [252]. A similar study involving the identification of the aggregation intermediates in the presence of phospholipid membrane revealed that prefibrillar species contain two loop regions with residues 57 to 61 and 71 to 80 [305].…”
Section: Phase Separation and Nucleation: Molecular Basis Of Fibril Polymorphismmentioning
confidence: 93%
“…Moreover, the structured β-sheet from the residues 74-79 is absent from its NAC domain (residues [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], suggesting PMFs to be less ordered fibril types. On the contrary, morphologically and structurally distinct HMFs are more compact and well-ordered with a stable fibril core [252]. These contain highly exposed hydrophobic surfaces and are potentially more toxic than less ordered PMFs.…”
Section: Phase Separation and Nucleation: Molecular Basis Of Fibril Polymorphismmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Because fibrils are polymorphic, the number of conformations available to a single peptide sequence can be extremely large. 13 As recent studies have shown that structural variants can display differing phenotypes and disease subtypes, [23][24][25][26][27] the large number of possible fibril conformations complicates the development of effective therapeutics and hinders our understanding of the role of fibrils in disease progression.…”
Section: Introductionmentioning
confidence: 99%